The state-constituted market economy - Weber, Isabella,Qi, Hao (University of Massachusetts Amherst, 2022)
China has created a distinct economic system. Yet despite a growing literature with valuable contributions on the institutional arrangements under 'capitalism with Chinese characteristics', the precise economic mechanisms underpinning China's state-market relations remain undertheorised. In this paper we develop a conceptual framework of what we call China's state-constituted market economy. We define essential as 'systemically significant from the perspective of the state'. We argue that the Chinese state 'constitutes' the market economy by creating, participating and steering markets for essentials in order to stabilise and guide the economy as a whole. We draw on China's statecraft tradition as well as on proposals for financial policy reform in the US to conceptualise the state market-constitution in China.
10.7275/kj02-f646
Keywords: Graue Literatur; China; state-market relations; varieties of capitalism; state capitalism; economic stabilisation; market creation